Competencies of Managers in Industry 4.0 In the Perception of the Senior Management Staff – Results of the Qualitative Research - Joanna M. MOCZYDLOWSKA; Karol KOWALEWSKI (Communications of International Proceedings, 2020)
The aim of the article is to systematize knowledge of key managerial competencies in enterprises 4.0 as well as to learn about opinions on this subject expressed by the management staff from the enterprise sector. The first part of this paper presents considerations about managerial competencies. Next, the origin and essence of the concept Industry 4.0” were described. The aim of the empirical part is to solve the following research problem: what is the opinion of the senior management of large and medium-sized business entities about managerial competencies important in the context of changes resulting from the development of Industry 4.0? The article contains the results of research carried out using the desk research method and focus group interview (FGI). The empirical material allows for the conclusion that requirements for the competencies of the senior management are very high. Their broad, interdisciplinary knowledge of new technologies and the business opportunities that emerge from using them, must go hand in hand with communication skills and sensitivity to the needs of others. Impersonal analytical and strategic thinking must be supported by flexibility and creativity, commitment in building relationships (often virtual) and bold leadership in a dispersed team. Creating ambitious, bold visions of the enterprise development must be based on independence, mental resilience and self-discipline, but also on openness to various points of view. Due to the limitation of research to Polish managers, we treat their results as preliminary and requiring continuation.
Keywords: competencies; industry 4.0; senior management staff.